Efficient Generation of Coherent Stokes Field in Hydrogen Gas-Filled Hollow Core Photonic Crystal Fibres - Thai, Thanh Doan; Ho, Quy Quang; Nguyen, Thang Manh (Communications in Physics, 2020)
In this paper, we study of the coherent Stokes generation in a transient Raman regime by Hydrogen gas-filled hollow-core photonic crystal fibres (HC-PCFs) configuration. The temporal and spatial evolution of the pump and Stokes field envelopes as well as the coherence and population inversion is numerically observed. The influence of the pump pulse width and gas pressure on the energy exchange along fiber and Stokes generation efficiency is investigated.